Noxious Weed Species Monochoria vaginalis Resistant to Synthetic Auxin and Acetolactate Synthase Inhibitor Herbicides - Ryan Widianto; Denny Kurniadie (Universitas Sebelas Maret, 2024)
Monochoria vaginalis (Burm. f.) C. Presl is a dominant weed in paddy rice cultivation, significantly threatening productivity and farming sustainability. In Subang, Indonesia, synthetic auxin and acetolactate synthase (ALS) inhibitors are commonly used to control M. vaginalis. However, farmers have currently reported declining efficacy of these herbicides. Therefore, this study aimed to confirm the resistance of M. vaginalis to the early post-emergence application of synthetic auxin and ALS inhibitors. Plant bioassays were conducted using the pot test method to determine resistance level. Herbicides were applied 2 weeks after planting M. vaginalis at 0.25, 0.5, 1.0, 2.0, 4.0, and 8.0 times the recommended dose, and untreated plants as control. Herbicides tested were 2,4-D, bensulfuron-methyl, bispyribac sodium, penoxulam, and sulfentrazone. The results obtained based on resistance index values (RI) showed that M. vaginalis populations from Kediri and Gandasari, Subang, had moderately to high resistance to 2,4-D (RI: 8.15 and 13.0) and bensulfuron-methyl (RI: 205.61 and 21.80). Weed was moderately resistant to bispyribac sodium (RI of Kediri biotype: 8.79) and had low to moderate resistance to penoxulam herbicides (RI: 8.94 and 3.56). In contrast, M. vaginalis-resistant biotypes remained susceptible to sulfentrazone (protoporphyrinogen oxidase/PPO inhibitors) herbicide. A significant increase in GR50 was observed between 28 and 56 days after herbicide application, signifying enhanced regrowth. The resistance of M. vaginalis to synthetic auxin and ALS inhibitors presents the need for farmers to consider alternative herbicides, such as PPO inhibitors, to prevent the development of resistant weeds.